Cervico-Vaginal Multiple Leiomyomas in a Labrador Dog: A Case Report - Dhoke, V. S.; Hedau, Madhuri; Joshi, M. V. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Leiomyomas are common in the canine female reproductive tract and accounts for 2.4% of all canine neoplasms (Hulland, 1978). Primary vaginal tumors are rare. They are usually secondary to either cervical or vulval lesions. In the vagina, leiomyoma usually presents as a solid single nodule mostly, firm consistency, brown color. In bitches, the tumor appears at middle and old age. Preoperative diagnosis of leiomyoma is challenging. Therefore leiomyoma is often diagnosed during postoperative histologic evaluation. Despite this, there are very few reports of them, apart from occasional surgical or clinical articles. The aim of this paper is to report a case of cervico-vaginal multiple leiomyoma in Labrador bitch.